Preparation method of pH-responsive ethyl methacrylate-acrylate copolymer enteric coating

By optimizing the formulation and preparation process of methacrylic-ethyl acrylate copolymer, a pH-responsive enteric coated material was developed, which solved the problem of inaccurate and poor stability of the dissolution rate control of existing materials under different pH conditions, and achieved accurate release of drugs in specific intestinal segments and high stability and low cost production of materials.

CN119899307APending Publication Date: 2025-04-29JIANGXI ALPHA HI TECH PHARMA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411800549.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing enteric coated materials have inaccurate dissolution rate control under different pH conditions, poor stability, complex preparation process and high cost, making it difficult to meet the needs of accurate release of drugs in specific intestinal segments.

Method used

Using pH-responsive methacrylic-ethyl acrylate copolymer, enteric coated materials that can remain insoluble in gastric acid and quickly dissolve in the intestinal alkaline environment by optimizing the formulation and preparation process of the copolymer.

Benefits of technology

Accurate drug release control at different pH environments is achieved, the stability and biocompatibility of the material is improved, the preparation process is simplified and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899307A_ABST
    Figure CN119899307A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating material, the enteric coating is prepared through an emulsion polymerization process, and methacrylic acid (MAA) and ethyl acrylate (EA) are used as monomers; and carrying out semi-continuous polymerization under the conditions of a reactive emulsifier containing sulfonate anions and a'starvation 'dropwise adding monomer to obtain stable copolymer latex. The copolymer latex is dissolved when the pH value is greater than 6.2, and is suitable for enteric drug coating membrane materials. The thermal property and the mechanical property of the copolymer can be optimized by regulating and controlling the MAA content and the plasticizer addition amount, so that the copolymer has good flexibility while the acid resistance is ensured. The preparation process is simple, and the obtained enteric coating film has excellent pH responsiveness, flexibility and acid resistance and is suitable for coating application of various oral medicines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pharmaceutical preparations, and in particular relates to a method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating. Background Art

[0002] Acrylic copolymers have been widely used in drug controlled release systems, enteric coating materials, adhesives and transdermal patches due to their excellent biocompatibility, good mechanical properties and adjustable drug release characteristics. Traditional enteric coating materials mostly use polymer materials such as cellulose acetate, chitosan, and acrylic resin. These materials can effectively protect drugs from being decomposed by gastric juice and gradually release drugs in the alkaline environment of the intestine to achieve controlled release or sustained release. However, existing enteric coating materials have the following problems: First, under different pH conditions, the dissolution rate of the material is not accurately controlled, resulting in too fast or too slow drug release, affecting the efficacy; second, the coating material has poor stability in long-term storage or complex in vivo environments, and is prone to physical or chemical degradation; finally, the traditional preparation process is complex, time-consuming and costly, which is not conducive to large-scale production.

[0003] Enteric coatings currently on the market are mainly based on acrylic resins, but their performance improvements and production process upgrades have not yet been solved. For example, the release of many materials in the intestine is not precise enough, especially for some drugs that need to be released in specific intestinal segments, the existing coating materials are difficult to meet the needs of such precise control. In addition, how to simplify the preparation process and reduce production costs while improving the mechanical strength, dissolution rate and pH responsiveness of the coating material has become a technical problem in the field of pharmaceutical preparations. Therefore, the development of an enteric coating material with high pH responsiveness, excellent biocompatibility and stability can not only significantly improve the accuracy and effect of drug release, but also reduce production costs, and has important application prospects.

[0004] Based on this, the present invention provides a method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating, which significantly improves the responsiveness and stability of the material under different pH environments by optimizing the formula and preparation process of the copolymer, thereby solving the deficiencies in the prior art. This new material can remain insoluble in gastric acid and accurately release drugs in an alkaline environment in the intestine, and the preparation process is simple, low-cost, suitable for large-scale production, and has important application value. Summary of the invention

[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating, which has the advantages of simple process and low equipment requirements, can achieve precise drug release control under different pH environments, and improve the stability and biocompatibility of the material.

[0006] The object of the present invention is achieved by the following technical scheme: A method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating comprises the following steps:

[0007] Step 1, preparation of copolymer monomer solution: methacrylic acid, ethyl acrylate and initiator are mixed in a certain proportion, and a proper amount of solvent is added to prepare a uniform monomer solution, wherein methacrylic acid accounts for 20%-40% and ethyl acrylate accounts for 60%-80%.

[0008] Step 2, copolymerization reaction: the monomer solution prepared in step 1 is subjected to free radical polymerization reaction under nitrogen protection to prepare a copolymer, the reaction temperature is controlled at 60° C.-80° C., and the reaction time is 4-6 hours, until the solution reaches the desired viscosity.

[0009] Step 3, forming the coating material: the obtained copolymer solution is mixed with a plasticizer, a stabilizer, and a pH sensitive agent, and after being fully stirred, it is evenly coated on the surface of the drug particles or tablets by a coating method, and after drying, a pH-responsive enteric coating is formed.

[0010] In the preparation method of the pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating, the initiator can be selected from dicumyl peroxide, azobisisobutyronitrile (AIBN) or potassium persulfate, and the amount used is 0.1%-1% of the total weight of the monomers.

[0011] In the above method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating, the plasticizer is triacetin or dibutyl phthalate, and the amount used is 5%-15% of the weight of the copolymer.

[0012] Compared with the prior art, the advantages of the present invention are: by reasonably selecting the ratio of copolymer monomers and initiators, the prepared coating material can remain insoluble in gastric acid, but quickly dissolve in the alkaline environment of the intestine, thereby achieving precise controlled release of the drug; in addition, the method is simple and easy to operate, suitable for large-scale production, and significantly improves the stability of the coating material and the accuracy of drug release control, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1Scanning electron micrographs of the enteric coating of the prepolymer in Example 1 of the present invention (50 mol% MAA, 10 wt% (polymer dry basis) TEC): (a) surface (b) cross section (c) partial enlargement of the cross section (d) partial enlargement of the cross section of the enteric coating layer DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0015] Example 1

[0016] (1) Preparation of copolymer latex

[0017] Add 500 grams of deionized water and 5 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 30 grams of methacrylic acid (MAA) and 30 grams of ethyl acrylate (EA) as reaction monomers. Subsequently, add 0.5 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0018] Start semi-continuous addition in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 1.5 g sodium octyl succinate sulfonate, 1 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" drop method to slowly drop into the reaction system over 7.5 hours, maintain 80 ° C and continue stirring. Add 0.2 g initiator APS every hour during the drop addition process. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0019] (2) Drying and performance testing

[0020] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0021] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in pH 1.2 simulated gastric fluid within 2 hours, and is completely dissolved in pH 6.8 simulated intestinal fluid within 30 minutes, which meets the requirements of enteric coating.

[0022] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 12MPa, which meets the mechanical property requirements of enteric coating materials.

[0023] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±5%.

[0024] Example 2

[0025] (1) Preparation of copolymer latex

[0026] Add 600 grams of deionized water and 4 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 25 grams of methacrylic acid (MAA) and 35 grams of ethyl acrylate (EA) as reaction monomers. Subsequently, add 0.4 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0027] Start semi-continuous dripping in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 2 g sodium octyl succinate sulfonate, 0.5 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" dripping method to slowly drip into the reaction system within 8 hours, maintain 80 ° C and continue stirring. During the dripping process, add 0.2 g initiator APS every hour. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0028] (2) Drying and performance testing

[0029] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0030] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in pH 1.2 simulated gastric fluid within 2 hours, and is completely dissolved in pH 6.8 simulated intestinal fluid within 30 minutes, which meets the requirements of enteric coating.

[0031] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 12.5MPa, which meets the mechanical property requirements of enteric coating materials.

[0032] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±5%.

[0033] Example 3

[0034] (1) Preparation of copolymer latex

[0035] Add 500 grams of deionized water and 3 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 30 grams of methacrylic acid (MAA) and 30 grams of ethyl acrylate (EA) as reaction monomers. Then, add 0.3 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0036] Start semi-continuous addition in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 2 g sodium octyl succinate sulfonate, 0.5 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" drop method to slowly drop into the reaction system within 7 hours, maintain 80 ° C and continue stirring. Add 0.2 g initiator APS every hour during the drop addition process. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0037] (2) Drying and performance testing

[0038] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0039] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in pH 1.2 simulated gastric fluid within 2 hours, and is completely dissolved in pH 6.8 simulated intestinal fluid within 30 minutes, which meets the requirements of enteric coating.

[0040] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 11.8MPa, which meets the mechanical property requirements of enteric coating materials.

[0041] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±4%.

[0042] Example 4

[0043] (1) Preparation of copolymer latex

[0044] Add 600 grams of deionized water and 4.5 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 40 grams of methacrylic acid (MAA) and 20 grams of ethyl acrylate (EA) as reaction monomers. Subsequently, add 0.5 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0045] Start semi-continuous addition in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 2 g sodium octyl succinate sulfonate, 0.5 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" drop method to slowly drop into the reaction system within 7 hours, maintain 80 ° C and continue stirring. Add 0.2 g initiator APS every hour during the drop addition process. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0046] (2) Drying and performance testing

[0047] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0048] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in pH 1.2 simulated gastric fluid within 2 hours, and dissolves slowly in pH 6.8 simulated intestinal fluid, which does not meet the requirements of enteric coating.

[0049] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 10MPa, which does not meet the mechanical property requirements of enteric coating materials.

[0050] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±8%.

[0051] Example 5

[0052] (1) Preparation of copolymer latex

[0053] Add 500 grams of deionized water and 3.5 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 35 grams of methacrylic acid (MAA) and 25 grams of ethyl acrylate (EA) as reaction monomers. Then, add 0.5 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0054] Start semi-continuous dripping in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 2 g sodium octyl succinate sulfonate, 0.5 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" dripping method to slowly drip into the reaction system within 8 hours, maintain 80 ° C and continue stirring. During the dripping process, add 0.2 g initiator APS every hour. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0055] (2) Drying and performance testing

[0056] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0057] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in simulated gastric fluid at pH 1.2 within 2 hours, and is almost insoluble in simulated intestinal fluid at pH 6.8.

[0058] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 9MPa, which does not meet the mechanical property requirements of enteric coating materials.

[0059] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±6%.

[0060] Example 6

[0061] (1) Preparation of copolymer latex

[0062] Add 450 grams of deionized water and 2.5 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 20 grams of methacrylic acid (MAA) and 40 grams of ethyl acrylate (EA) as reaction monomers. Subsequently, add 0.4 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0063] Start semi-continuous addition in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 2 g sodium octyl succinate sulfonate, 0.5 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" drop method to slowly add to the reaction system within 6.5 hours, maintain 80 ° C and continue stirring. During the drop process, add 0.2 g initiator APS every hour. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0064] (2) Drying and performance testing

[0065] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0066] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in simulated gastric fluid at pH 1.2 within 2 hours, and dissolves rapidly in simulated intestinal fluid at pH 6.8.

[0067] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 13MPa, which meets the mechanical property requirements of enteric coating materials.

[0068] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±4%.

[0069] Example 7

[0070] (1) Preparation of copolymer latex

[0071] Add 550 grams of deionized water and 3 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 35 grams of methacrylic acid (MAA) and 25 grams of ethyl acrylate (EA) as reaction monomers. Subsequently, add 0.6 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0072] Start semi-continuous dripping in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 2 g sodium octyl succinate sulfonate, 0.5 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" dripping method to slowly drip into the reaction system within 8 hours, maintain 80 ° C and continue stirring. During the dripping process, add 0.2 g initiator APS every hour. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0073] (2) Drying and performance testing

[0074] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0075] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in simulated gastric fluid at pH 1.2 within 2 hours, and dissolves rapidly in simulated intestinal fluid at pH 6.8.

[0076] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 14MPa, which meets the mechanical property requirements of enteric coating materials.

[0077] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±3%.

[0078] Comparative Example 1

[0079] (1) Preparation of copolymer latex

[0080] Add 500 grams of deionized water and 5 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 50 grams of methacrylic acid (MAA) and 10 grams of ethyl acrylate (EA) as reaction monomers. Then, add 0.5 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0081] Start semi-continuous addition in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 1.5 g sodium octyl succinate sulfonate, 1 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" drop method to slowly drop into the reaction system over 7.5 hours, maintain 80 ° C and continue stirring. Add 0.2 g initiator APS every hour during the drop addition process. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0082] (2) Drying and performance testing

[0083] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0084] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material does not dissolve in pH 1.2 simulated gastric fluid within 2 hours, and is almost insoluble in pH 6.8 simulated intestinal fluid, which meets the requirements of enteric coating.

[0085] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 7MPa, which does not meet the mechanical property requirements of enteric coating materials.

[0086] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±10%.

[0087] Comparative Example 2

[0088] (1) Preparation of copolymer latex

[0089] Add 500 grams of deionized water and 5 grams of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer to the reactor and stir until completely dissolved. Then, add 10 grams of methacrylic acid (MAA) and 50 grams of ethyl acrylate (EA) as reaction monomers. Subsequently, add 0.5 grams of ammonium persulfate (APS) as an initiator, heat and stir at a constant temperature of 80°C under nitrogen protection, and perform a prepolymerization reaction for 30 minutes to generate a seed emulsion.

[0090] Start semi-continuous addition in the seed emulsion, mix 100 g MAA and 100 g EA in a 1:1 ratio, add emulsifier (2 g sodium dodecyl sulfate, 1.5 g sodium octyl succinate sulfonate, 1 g polyoxyethylene sorbitan monooleate), and prepare a monomer mixed solution. Use the "starvation" drop method to slowly drop into the reaction system over 7.5 hours, maintain 80 ° C and continue stirring. Add 0.2 g initiator APS every hour during the drop addition process. After the polymerization reaction is completed, continue stirring and heating for 1 hour to ensure complete conversion of the monomer. The reaction system is cooled to room temperature, and the unreacted monomers and residues are removed by centrifugation to obtain a pure copolymer latex.

[0091] (2) Drying and performance testing

[0092] The obtained copolymer latex was spray dried to obtain dry powder for use as enteric coating material. The performance test results are as follows:

[0093] Solubility test: According to the test standards of the "Chinese Pharmacopoeia" (2020 edition), the prepared coating material dissolved in pH 1.2 simulated gastric fluid within 2 hours, which does not meet the requirements of enteric coating.

[0094] Tensile strength test: According to GB / T 1040.3-2006 standard, the tensile strength test result of the coating film is 5MPa, which does not meet the mechanical property requirements of enteric coating materials.

[0095] Thickness uniformity test: According to GB / T 13477.3-2002 standard, the thickness uniformity of the coating film is good, and the deviation does not exceed ±12%.

[0096] After the ratio of MAA to EA was adjusted, the pH responsiveness and mechanical properties of Comparative Examples 1 and 2 decreased significantly. The high MAA content (Comparative Example 1) resulted in excessive cross-linking, making the material difficult to dissolve in intestinal fluid; the high EA content (Comparative Example 2) made the material too soft, with insufficient mechanical strength and dissolved in gastric fluid, losing its enteric function.

[0097] Table 1 Summary of performance test results of different embodiments and comparative examples

[0098] Example / Comparative Example Solubility test (pH 6.8) Tensile strength(MPa) Thickness uniformity (deviation) Pass / Fail Example 1 qualified 12.0 ±5% qualified Example 2 qualified 12.5 ±5% qualified Example 3 qualified 11.8 ±4% qualified Example 4 Failure 10.0 ±8% Failure Example 5 Failure 9.0 ±6% Failure Example 6 qualified 13.0 ±4% qualified Example 7 qualified 14.0 ±3% qualified Comparative Example 1 Failure 7.0 ±10% Failure Comparative Example 2 Failure 5.0 ±12% Failure

[0099] The above description is only part of the embodiments of the present invention and is not intended to limit the present invention. All equivalent changes and modifications made according to the content of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating material, characterized in that: The following steps are involved: Step 1, preparation of seed emulsion: add an appropriate amount of deionized water into a reactor, add 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as a stabilizer, stir and dissolve, add methacrylic acid (MAA) and ethyl acrylate (EA) as reaction monomers in sequence, then add initiator ammonium persulfate (APS), heat at a constant temperature of 80° C. under nitrogen protection, keep stirring, carry out prepolymerization reaction, react for about 30 minutes, and obtain seed emulsion. Step 2, semi-continuous dropwise polymerization: In the seed emulsion obtained in step 1, a semi-continuous dropwise addition process is started. MAA and EA monomers are mixed in a ratio of 1:1, and then a monomer mixed solution is prepared with an emulsifier mixture (sodium dodecyl sulfate, sodium octyl succinate sulfonate and polyoxyethylene sorbitan monooleate). The monomer mixed solution is slowly added to the reactor by the "starvation" dropwise addition method, and the dropwise addition time is controlled to be 7.5 hours. At the same time, the system temperature is maintained at 80°C, and the system is kept fully stirred to ensure that the reaction proceeds uniformly. During the dropwise addition process, the initiator (ammonium persulfate) in the system is added in small amounts until all monomers are added to obtain a copolymer emulsion. Step 3, post-treatment and latex purification: After the polymerization reaction is completed, continue to stir and heat for 1-2 hours to ensure that all monomers are completely converted. After the reaction is completed, the system is cooled to room temperature, and unreacted monomers and initiator residues are removed by centrifugation or ultrafiltration to obtain pure copolymer latex. Step 4, drying and powder preparation: the obtained copolymer latex is made into dry powder by spray drying or freeze drying process for use as enteric coating material.

2. The method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating according to claim 1, characterized in that: The emulsifier is a mixture of sodium dodecyl sulfate (SDS), sodium octyl succinate sulfonate (AOT) and polyoxyethylene sorbitan monooleate (Tween 80), with the mass ratio of the three being 1:1:

3. This formula can provide a stable emulsification environment, ensure uniform distribution of monomers and promote smooth polymerization reaction.

3. A method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating according to claim 1 or 2, characterized in that: The initiator is a mixed system of ammonium persulfate (APS) and sodium sulfite, wherein the amount of APS is 0.1wt%-0.2wt% of the total weight of the monomer, and the sodium sulfite is used as a chain transfer agent to regulate the molecular weight and distribution of the polymer.

4. A method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating according to claim 1 or 2, characterized in that: The solid content of the obtained copolymer latex is 30wt%-40wt%, wherein the particle size of the copolymer ranges from 100 to 200 nanometers, the particle size measured by dynamic light scattering method is uniform, and the conversion rate of the latex system reaches more than 99.5%.

5. The method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating according to claim 1 or 2, characterized in that: The copolymer dissolves rapidly when the pH value is greater than 6.2, and is used for preparing enteric drug coatings, which can achieve effective intestinal directional release of drugs, significantly improve the bioavailability of drugs, and provide better coating stability and mechanical strength.

6. The method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating according to claim 1 or 2, characterized in that: The pH responsiveness of the copolymer is provided by the weakly acidic groups (such as carboxyl groups) contained in the copolymer chains. When the pH value of the external environment exceeds 6.2, these carboxyl groups are ionized, causing the copolymer to dissolve, thereby controlling the drug release.

7. The method for preparing a pH-responsive methacrylic acid-ethyl acrylate copolymer enteric coating according to claim 1 or 2, characterized in that: The copolymer enteric coating can be applied to enteric film coatings of various solid drugs, such as tablets, capsules, etc. It has excellent acid resistance, can maintain the integrity of the drug in the gastric acid environment, avoid premature release of the drug, and quickly dissolve and release the drug in the small intestine.